UTILIZATION OF HEALTH SERVICES AT COMMUNITY HEALTH CENTERS: A REVIEW - Usman, Usman; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT The Indonesian government's response to the new normal, particularly in the health services sector during the Covid-19 era, has prompted a transformative shift, emphasizing the need for health professionals to adeptly integrate technology, information, and communication. This shift is fueled by evolving consumer expectations, marked by a heightened demand for accessible health services addressing immediate concerns and preventing illness. The implications of this transition extend to the accessibility of health facilities, funding sources, and overall service costs. This research aimed to explores the behavioral patterns influencing individuals' utilization of community health centers in the new normal. Using a modified systematic literature review, the study synthesizes existing knowledge on factors shaping health service utilization, focusing on motivations for seeking healthcare due to pain or discomfort. Employing a modified systematic literature review methodology, the research analyzed relevant papers on individuals utilizing community health centers, emphasizing the new normal's impact on access, funding sources, and cost implications of health services. Findings highlight a prominent motivation—alleviating pain or discomfort—consistently emerging across the literature. In the evolving new normal landscape, individuals accessing community health centers rely substantially on services to alleviate pain, emphasizing the need for tailored health service delivery aligned with proactive health-seeking behavior. Recommendations include health service providers adapting practices to evolving consumer expectations through potential technology integration, improved access, and transparent communication on costs. Ongoing research and monitoring of consumer behavior remain essential for sustained effectiveness and responsiveness in the dynamic new normal landscape. Keywords: Health services, Community Health Center